Laporan Kasus: Kehamilan 36 Minggu dengan Ketuban Pecah Dini dan Skizofrenia tanpa Pengobatan - Nirfandi, Haikal; Sari, Ratna Dewi Puspita; Saragih, Reynhard Theodorus (Medula, 2025)
Perinatal mental disorders, including schizophrenia, increase the risk of complications during pregnancy, labor, and neonatal health. Schizophrenia in pregnant women can lead to premature rupture of membranes, preterm labor, and fetal distress. The use of antipsychotics during pregnancy is also associated with an increased risk of obstetric and metabolic side effects. This case report presents a 38-year-old pregnant woman, G5P4A0, at 36 weeks of gestation, with a seven-year history of untreated schizophrenia, who presented with premature rupture of membranes. Examination revealed stable maternal condition, although fetal distress was suspected. The patient was treated with intravenous fluids, antibiotics, tocolytics, and antipsychotics (haloperidol, CPZ, risperidone), and subsequently underwent cesarean section due to fetal distress. Women with schizophrenia are at higher risk of premature rupture of membranes, fetal distress, and preterm delivery. Antipsychotic use during pregnancy also increases the risk of complications such as gestational diabetes and metabolic disorders. The management of pregnant women with mental disorders requires a multidisciplinary approach involving psychiatrists, obstetricians, and neonatologists to minimize risks to both mother and fetus. Close monitoring of maternal medical conditions, medication dosages, and fetal growth is essential to optimize care, and decisions regarding the mode of delivery should consider both psychiatric and obstetric conditions.